A corpus-driven critical discourse analysis of news reports on disabled women - Ran Yangxia; Zhao Mengdan (Cogent Arts & Humanities)
Words engender consciousness, and news reporting, as an important medium for the dissemination of discourse, shapes public cognition imperceptibly. As a marginalized group in patriarchal societies, disabled women have received relatively little attention. Therefore, using a corpus-driven critical discourse analysis, this study investigates the overall media representation of disabled women in Chinese news reports (2013–2023), along with the underlying cognitive and social factors. It reveals that Chinese news reporting prefers the social model of disability, which tends to narrate from the perspective of society and caregivers. This is also evidenced by the use of different personal pronouns. Second, in the view of semantic preference, it is apparent that expressions associated with disabled women often carry derogatory and negative emotional connotations, such as ‘left-behind’ and ‘poor’. However, the overall semantic prosody presented in the news is primarily positive, advocating for societal attention and assistance towards this group. Finally, through the analysis of thematic words and high-frequency collocations, Chinese reports touch upon topics related to sexuality and marriage in the news descriptions of intellectually disabled women, potentially hinting at the discourse rights of this segment of the population.